Evaluation of lifestyle characteristics among patients with metabolic syndrome in alnajaf 2022 - Alaa, Rand (Karbala Journal of Medicine, 2024)
Abstract Background: Metabolic syndrome (MetS) is a cluster of various metabolic risk factors that occur in the same individual,including central obesity, hypertension,hyperglycemia,and dyslipidemia. It contributes to cardiovascular morbidity and mortality, and has been associated with multiple cancers including breast, pancreatic, colon, and liver cancer, Globally, it is estimated that 25% of the adult population can be characterized as having MetS. Obesity is fundamental to MetS, and with the global obesity epidemic, the prevalence of metabolic syndrome is rising rapidly in the both the developed and developing world. Objectives: 1.To evaluate the demographic and clinical charecteristics of metabolic syndrome patients. 2.To assess the association of some lifestyle risk factors and the components of metabolic syndrome. 3.To assess gender differences regarding demographic, clinical and lifeslyle risk factors. Method: A cross sectional study was carried out in Alsader Teaching Hospital in AL-Najaf-Ashraf province/Iraq and Specialist Center Of Endocrine Disease And Diabetes, aimed to explore the lifestyle characteristics in metabolic syndrome patients and associated risk factors.Indiviuals were included in the current study , who their nationality was Iraqi and accepted to take part in this study. Each patient data was collected through a 15-minuts direct interview using a questionnaire. All cases completed a detailed questionnaire that included information about demographic, anthropometric measurements, biochemical tests, Physical measurements and lifestyle informations by health care professionals. They were screened for MS criteria. The diagnosis of metabolic syndrome (MetS) was confirmed according to the recently (2009) revised International Diabetes Federation definition, according to which it is necessary to present three of the five risk factors (WC ≥94 cm in men and ≥80 in women; TG ≥ 150 mg/dL (1.7 mmol/L); HDL-c < 40 mg/dL (1.0 mmol/L) in men and <50 mg/dL (1.3 mmol/L) in women; systolic blood pressure ≥ 130 and diastolic ≥ 85 mmHg); fasting glucose ≥ 100 mg/dL). Result: This study showed that irregular physical activity in this representative sample of the selected Iraqi population was about half of the study participants, these findings confirm the high prevalence of physical inactivity among adult males, females and adolescents reported by previous studies Conclusion: The prevalence of MetS is reaching epidemic proportions worldwide and is influenced by various factors. As we mentioned,the metabolic syndrome is high in all previous studies done in Iraq, regardless of the criteria used. Iraq has a high level of irregular physical activity in various population groups, public heath efforts to promote weight control and physical activity should be given a high attention in all country. Overeating, decreased physical activity, cultural expectations and educational contribute to sex and geographic disparities in MetS, in addition to hormonal and genetic factors. However, in no country is the health care system geared to cope with this medical crisis. Key words: Metabolic syndorme ( MetS), Type 2 diabetes, Physical activity, BMI, Iraq, Obesity, Waist circumference, Lifestyle characteristics.